Tinjauan Yuridis Penetapan Surat Perintah Penghentian Penyidikan PPAT terhadap Akta Jual Beli - Amanda, Utari; Muchtar, Syamsuddin; Marwah, Marwah (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to examine the accountability of the Land Deed Official for the Sale and Purchase Deed it made and what is the basis for stopping the investigation of the Land Deed Official who has made the Sale and Purchase Deed No. 123/2014. This research was conducted using a normative legal research method with a statute approach. The method of analysis in this study is to use qualitative analysis. The results of this study indicate that the responsibility of the Land Deed Official to the Sale and Purchase Deed can be categorized into two things, namely legal responsibility and ethical responsibility. Furthermore, legal responsibilities can also be divided into three categories: administrative law, civil law, and criminal law. Meanwhile, the issuance of the Warrant of Termination of Investigation Number: S.Tap/70.6/VIII/2019 is based on the findings of the facts from the Palu Resort Police investigation, that the Parties knew and agreed to include the price for a piece of land in the Sale and Purchase Deed No. 123/2014. Therefore, the Land Deed Official cannot be subject to a crime based on Article 266 of Law no. 1 of 1960 because the Land Deed Official had carried out their duties properly. In addition, the Land Deed Official is the person who was ordered (manus miniatra), and in criminal law, the person who is ordered cannot be held criminally responsible for his actions. Sale and Purchase Deed No. 123/2014 is also not used by the Land Deed Official to cause harm. So the case against Sale and Purchase Deed No. 123/2014 is declared unfit or cannot be continued. It is recommended that the Land Deed Official be more thorough and professional and be careful in carrying out the duties and authorities of his position, especially regarding the procedures for making the Land Deed Official deed to minimize errors regarding formal and material requirements.